Problem Hukum Regulasi LMK & LMKN Sebagai Pelaksanaan Undang-Undang Hak Cipta 2014 - Sardjono, Agus (Jurnal Hukum & Pembangunan, 2016)
UUHC 2014 has been effective since October 2014. The various clauses in the law still contains potential problems, especially those related to copyright in the music, because of its multiple interpretations. The multiple interpretations conditions especially with respect to the setting of the Collective Management Organization. Regulation of the Minister of Law and Human Rights No. 29 In 2014 it adds to the potential problems due to a few mistakes LMKN arrangements concerning the formation and powers rest upon to him. The problem was quite pronounced, since an doctrinal analysis. This paper attempts to reveal the problems in question